Study of Linear Attenuation Coefficient and Buildup Factor of Some Metals at 662 keV and 1332 keV - M, Sheela; Eshwarappa, K.M. (The Nucleus, 2024)
The nuclear shielding properties of some metals such as lead, copper, iron, aluminium, and carbon were studied using 3ʺ×3ʺNaI(Tl) scintillation detector by the evaluation of shielding parameters such as the linear attenuation coefficient and gamma-ray buildup factor. The linear attenuation coefficient of lead is very high compared to the other materials used for the study. The buildup factors of these materials were observed to increase with the increase in the thickness of the material. The value of the buildup factor is found to be high at 662 keV and low at 1332 keV. Moreover, the buildup factors of lead were significantly higher than those of other materials investigated in this study.